Overall Environmental Modelling of Newly Designed Curtain Wall Façade Configurations. Issue 1 (February 2013) - Kim, Gon; Lim, Hong Soo; Schaefer, Laura; Kim, Jeong Tai
There has been a rapidly growing interest among contemporary architects in recent years in the innovative use of curtain walls as a building enclosure. A curtain wall is a glass and metal skin that wraps the entire building in a continuous, transparent layer. This modern design provides a relatively desirable environment for the occupants. The glass façade allows light and diffused views into the surroundings during the day and can become a glowing and aesthetically pleasing aspect of the skyline at night. The key visual features of curtain walls are the glazing appearance and sightlines, but the window selection plays a key role in determining the overall building's environmental performance. The complex layering of glass should be strategic as well as artistic, balancing light and shade to optimize light and minimize heat gain. Recently, a series of curtain wall system have been developed with an emphasis on the technical issues, such as structural stability, energy efficiency, sustainable strategies, daylighting, and materials. This design case project explores in depth the overall environmental performance of the leading-edge curtain wall assemblies using computer programs such as Virtual Environment and Radiance, which allow estimation of total U-values and helps predict daylighting performance.